Effects of Inspiratory Muscle Training with Incentive Spirometry to Maximum Inspiratory Capacity and Quality of Life on Chronic Obstructive Pulmonary Disease Patients - Tresia Fransiska Ulianna Tambunan; Moerdjajati Angka; Anita Ratnawati; Zulkifi Amin (Indonesian Journal of Physical Medicine & Rehabilitation, 2013)
Objectives: to determine whether the incentive spirometry respiratory muscle training can increase the maximum inspiratory capacity, decrease difficulty of breathing, functional lung capacity and quality oflife according to St. George’s Respiratory Questionnaire on Chronic Obstructive Pulmonary Disease patients.Methods: an intervention pre-post and case control group of twenty subjects with mild COPD who came to Medical Rehabilitation Department. They divided into two groups: control group (10 subjects)and study group (10 subjects). All subjects underwent pre interventional test which are : maximum inspiratory capacity, dyspnoea rating scale, pulmonary functional test (PFT) and questionnaire forquality of life. The study group were given respiratory muscle training with incentive spirometry and breathing control exercise while the control group only given the breathing control exercise. After 8weeks, all participant underwent post interventional test. Every subject still using the basic medication.Results: There are statistically improvement of maximum inspiratory capacity, dyspnoea rating scale and quality of life in study group compare with the control group (p<0,05). Mean difference of SGRQbetween pre and post intervention shows significant results in activity, impact and total component (p<0,05) and there is no significant results on symptoms components (p>0,05). No changes were foundin FEV1% value with the study or control group (p>0,05).Conclusions: Combination between incentive spirometry respiratory muscle training and breathing control exercise can improve maximum inspiratory capacity, dyspnoea rating scale and quality of life inCOPD patients within 8 weeks.Keywords: COPD, Incentive spirometry muscle training, Maximum inspiratory capacity, Quality of life.